The Additives Influence on Heat-Conducting Properties of Aluminium Nitride Circuit Boards; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Karakulov A. S. Aleksandr Sergeevich; Gusev N. V. Nikolay Vladimirovich; Drozdov Yu. Yu. Yury Yurievich; Nikonova N. Y. (Materials and Technologies in Powder Metallurgy and Additive Manufacturing, 2016)
Title screen